2021
DOI: 10.3389/fmolb.2021.669361
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling a Hidden Event in Fluorescence Correlative Microscopy by AFM Nanomechanical Analysis

Abstract: Fluorescent imaging combined with atomic force microscopy (AFM), namely AFM-fluorescence correlative microscopy, is a popular technology in life science. However, the influence of involved fluorophores on obtained mechanical information is normally underestimated, and such subtle changes are still challenging to detect. Herein, we combined AFM with laser light excitation to perform a mechanical quantitative analysis of a model membrane system labeled with a commonly used fluorophore. Mechanical quantification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…A similar effect was recently visualized studying the interaction with Nile red hydrophobic staining agent on the DOPC bilayer, with and without laser illumination. 78 Using Nile red, the adhesion force increases in agreement with the presence of a dye overlayer on top of the DOPC molecules, improving their stability (breakthrough force and Young's modulus). On the other hand, when focusing the laser light on the bilayer, the DOPC structure weakens, leading to a decrease of mechanical parameters and adhesion force.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…A similar effect was recently visualized studying the interaction with Nile red hydrophobic staining agent on the DOPC bilayer, with and without laser illumination. 78 Using Nile red, the adhesion force increases in agreement with the presence of a dye overlayer on top of the DOPC molecules, improving their stability (breakthrough force and Young's modulus). On the other hand, when focusing the laser light on the bilayer, the DOPC structure weakens, leading to a decrease of mechanical parameters and adhesion force.…”
Section: Resultsmentioning
confidence: 87%
“…Here the force-indentation relationships can be employed to analyze the elastic properties of the lipid bilayers. First, we obtain the Young's modulus by fitting the Hertz model for a parabolic indenter to the force vs. indentation curves, with the finite-thickness correction valid for not bonded thin elastic layers supported on a solid substrate (eqn (1)): 59,72,78,79 where F is the applied force, δ is the indentation (not exceeding half the bilayer thickness h ), ν is the Poisson's ratio (set equal to 0.5), E is the Young's modulus of the lipid bilayer, and R is the radius of the spherical probe (set to its nominal value, R = 20 nm). The adimensional parameter represents the ratio of the contact radius to the bilayer thickness and is the driving parameter of the finite thickness correction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect was recently visualized studying the interaction with Nile red hydrophobic staining agent on DOPC bilayer, with and without laser illumination. 78 Using Nile red, the adhesion force increases in agreement with the presence of a dye overlayer on top of DOPC molecules, improving their stability (breakthrough force and Young's modulus). Oppositely, when focusing the laser light on the bilayer, the DOPC structure weakens, leading to a decrease of mechanical parameters and adhesion force.…”
Section: Adhesive and Electrostatic Behavior Of Dopc Bilayers Interac...mentioning
confidence: 88%
“…42,53,91 To support this hypothesis, we report that our research group recently investigated the interaction of a DOPC bilayer with a common lipid dye (Nile red). 78 These hydrophobic molecules are designed to target the lipid layer avoiding structural damage. AFM indentation indeed showed the presence of a stabilizing overlayer of dye on top of exposed leaflet causing an increase of thickness, breakthrough force and Young's modulus, similarly to Rotella et al 48 In a recent work, Kumari et al 91 showed that after 5 hours interaction with DOPC, [C4MIM][Cl] can overcome the interaction energy threshold, showing a dramatic decrease of stability and mechanical properties as a consequence of cation tails inserting in the bilayer.…”
Section: Mechanical Analysis Of Dopc Bilayers Interacting With Ilsmentioning
confidence: 99%